Evaluation of manganese superoxide dismutase and thioredoxin2 levels in asbestos-induced pleural mesothelioma - Abdullah Sivrikaya; Bayram Metin; Esma Menevse; Yavuz Selim Intepe; Ayse Yesim Gocmen (Medicine Science, 2020)
Asbestos is a mineral known as human carcinogenic material. Exposure to asbestos both in an occupational and environmental way causes asbestosis and mesothelioma. ROS contributes to the development of pulmonary-toxicity induced asbestos.We aimed to determine the levels of important mitochondrial substances such as manganese superoxide dismutase (MnSOD) and Thioredoxin (Trx2) in asbestosis and mesothelioma patients. The study was performed with the patients admitted to outpatient clinics of Chest Diseases and Thoracic Surgery, at Medicine Faculty, Bozok University. Group 1 (healthy control group, n=27): Consisting of healthy individuals (54.18±9.89 years old), Group 2 (patients group, n=34): Evaluation of clinical, pathological and radiological analysis, patients who defined as mesothelioma and/or pleural plaques and asbestosis (60.24±15.24 years old). Patients, who were not biopsied or not available for biopsy due to comorbid diseases, were not included in the study.Biochemical analysis was done in Selcuk University Medicine Faculty Research Laboratories.Serum Trx2 and MnSOD levels were determined by the Elisa method. The results of Trx2 were calculated as pg/µg protein. MnSOD samples were determined as ng/µg protein. MnSOD and Trx2 levels in the patients group were statistically lower than the levels of the healthy group (p=0.000, p=0.048), respectively.Trx2 levels were 1.74±0.33 pg/µg protein in a healthy group whereas were 0.89±0.10 pg/µg protein in asbestosis and mesothelioma group. Serum MnSOD levels were 1.38±0.24 and 0.29±0.11 ng/µg protein in healthy and patients groups, respectively.These significant changes in malignant mesothelioma patients reflect the impairment of the oxidant-antioxidant balance system. The study presents basic findings for the clinical meaning of mentioned biochemical parameters in mesothelioma patients. [Med-Science 2020; 9(4.000): 912-6]